Analysis of critical thinking and communication skills in geometric transformation problem solving using TransGeo application - Ilmi, Malika Kautsar; Syaifuddin, Mohammad; Susanti, Reni Dwi; Ummah, Siti Khoiruli (Jurnal Riset Pendidikan Matematika, 2022)
The research aims to analyze narratively critical thinking and communication skills using the Android-based TransGeo application on geometry transformation in junior high school. This study uses a qualitative with a descriptive method obtained from tests and interviews. The test contains contextual problems in the android application, while the interviews are based on student test answers. Then, test results are adjusted descriptively by presenting the achievement of each student to be categorized based on critical thinking and communication scoring. Next, one student was randomly selected from each category as the interview subject. The indicator of critical thinking skills is the most difficult to achieve in the fourth indicator. Students are less precise in writing conclusions related to the initial problem; the indicator that many students succeed is the first indicator where students have written what is known and asked in difficulties. The indicator of communication skills is the most difficult to achieve in the second indicator. Students did not describe or write mathematical sentences to present an explanation of the transformation type or final position area in the problem. Many students achieve the first indicator, where they have written what they know and are asked about.